2018
DOI: 10.1002/mrm.27534
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of magnetohydrodynamic effects in magnetic resonance electrical impedance tomography at ultra‐high magnetic fields

Abstract: Purpose Artifacts observed in experimental magnetic resonance electrical impedance tomography images were hypothesized to be because of magnetohydrodynamic (MHD) effects. Theory and Methods Simulations of MREIT acquisition in the presence of MHD and electrical current flow were performed to confirm findings. Laminar flow and (electrostatic) electrical conduction equations were bidirectionally coupled via Lorentz force equations, and finite element simulations were performed to predict flow velocity as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Double‐echo planar imaging 60 might help to reduce the sensitivity of the MR data to physiological field fluctuations, but likely has lower sensitivity to the current‐induced magnetic fields. Furthermore, ultrahigh‐field MRI, for example, at 7T or 9.4T, generally offers higher SNRs, 61 but also requires careful optimization of the imaging methods to achieve robust results 62 . Another important goal would be the extension to simultaneous multislice 63 or volume acquisition to obtain more complete information of the current‐induced magnetic field changes, which might help the accurate reconstruction of the TES currents and the conductivity distribution in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double‐echo planar imaging 60 might help to reduce the sensitivity of the MR data to physiological field fluctuations, but likely has lower sensitivity to the current‐induced magnetic fields. Furthermore, ultrahigh‐field MRI, for example, at 7T or 9.4T, generally offers higher SNRs, 61 but also requires careful optimization of the imaging methods to achieve robust results 62 . Another important goal would be the extension to simultaneous multislice 63 or volume acquisition to obtain more complete information of the current‐induced magnetic field changes, which might help the accurate reconstruction of the TES currents and the conductivity distribution in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ultrahigh-field MRI, for example, at 7T or 9.4T, generally offers higher SNRs, 61 but also requires careful optimization of the imaging methods to achieve robust results. 62 Another important goal would be the extension to simultaneous multislice 63 or volume acquisition to obtain more complete information of the current-induced magnetic field changes, which might help the accurate reconstruction of the TES currents and the conductivity distribution in the brain. However, maintaining the required sensitivity levels, image quality, and robustness to physiological noise within a larger brain volume might be challenging.…”
mentioning
confidence: 99%
“…Finally, Frauenrath et al suggested to use the characteristics of the increased MHD effect for gating [ 6 ] and several studies have investigated measuring and modelling of the MHD effects throughout the body [ 40 , 41 ]. These methods show promise, but are at an early stage of technical development.…”
Section: Discussionmentioning
confidence: 99%